Using Bayesian Network for Robot Behavior with Sensor Fault - Rezaee, A.; Raie, A.; Nadi, A.; Shiry, S. (Elektronika ir Elektrotechnika, 2011)
The paper discussed application of Bayesian network to learn behavior of mobile robot in presence of fault sensor. Theoretical and practical are considered for checking the results. Robot’s model was considered as Bayesian model that each value of CPD was learned. This framework shows that can be work in real environment with noisy sensor. Ill. 12, bibl. 7, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.152